Hospitals in Iran and India, 1500-1950s - Speziale, Fabrizio, 1968- (Iran studies, 2012)
This work presents a significant panorama of studies on the history and role of hospitals in the Indo-Iranian world during the early modern and the modern periods when both traditional Avicennian medicine as well as Western medicine were practiced.